Factors associated with the depression among people with disabilities: A cross-sectional study in Chinese communities of Shanghai. Issue 47 (20th November 2020) - Bi, Yahong; Zhao, Xincai; Zhou, Yanyan; Lao, Limin; Jiang, Sunfang
Abstract : Abstract: Depression has become a growing health issue in the world and is projected to become a leading cause of global burden. However, there is little scientific research on the factors associated with depression in people with disabilities in China. In this cross-sectional study, we aimed to explore the prevalence and related factors of depression among people with disabilities in communities in mainland China. Participants with disability certificates were recruited via face-to-face interviews to complete questionnaires. Contents include participants' demographic characteristics, the Modified Barthel Index (MBI), chronic medical history, and the Patient Health Questionnaire-9 (PHQ-9). A total of 1815 participants (M age = 60.35 ± 13.66) whose questionnaires are eligible were finally included. Among them the incidence rate of depressive symptoms was up to 39.9%. Multifactor regression analysis showed that grade I disability (odds ratio (OR) = 1.37, P < .05), impairment activities of daily living (OR = 3.23, P < .001), diabetes (OR = 1.43, P < .05), and hyperlipidemia (OR = 1.59, P < .001) were associated with depression in the disabled. However, intelligence disability is a protective factor of depression (OR = 0.69, P < .05). The data demonstrates that the depression of the disabled should arouse the attention of our society. Furthermore, the interventions to disability degree, impairment activities of daily living, diabetes, and hyperlipidemia may help to improve the mental health of the disabled people.